Bank Competition, Risk Taking, and their Consequences : Evidence from the U.S. Mortgage and Labor Markets - Xiaochen Feng, Alan. (Washington, D.C. : International Monetary Fund, 2018)
Bank competition can induce excessive risk taking due to risk shifting. This paper tests this hypothesis using micro-level U.S. mortgage data by exploiting the exogenous variation in local house price volatility. The paper finds that, in response to high expected house price volatility, banks in U.S. counties with a competitive mortgage market lowered lending standards by twice as much as those with concentrated markets between 2000 and 2005. Such risk taking pattern was associated with real economic outcomes during the financial crisis, including higher unemployment rates in local real sectors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet